Economic crisis, citizens' perception and media - Sobrados León, Maritza (2010)
After a long period of cconomic boom, European counrries are living an economic crisis thar has shaken the foundations of the European Un ion. Spain, Greece and Portugal arerhe counrries that have suffered the crisis; in this article I will refer to the economic siruarion in Spain and how the dominant reference newspapers have reponed rhis crisisro a population away and linle aware of and concerned about economic issues and worried by the most nearby consequences: unemployment, loss of purchasing power, pooraccess ro morrgage loans, etc.